PERKEMBANGAN TERKINI PATOGENESIS DAN TATALAKSANA SELULIT (Perhimpunan Dokter Spesialis Kulit dan Kelamin Indonesia (PERDOSKI), 2022)
Cellulite is characterized by skin topography alterations that have been described as peau d'orange, cottage cheese or mattress-like appearance. All age groups and both sexes could have cellulite, especially post-puberty females. Cellulite is more common seen in Caucasian than Asian woman. Based on the study of woman skin anatomy, fat cells and connective tissue are aligned vertically so that fat cells could protrude into the skin layer and cause cellulite. The pathogenesis of cellulite is controversial and the etiology are multifactorial. If the etiopathogenesis are already known, more effective treatments could be developed. Three main cellulite theories are adipocyte accumulation, water retention and septa fibrosis. Several combination theories associated with cellulit include genetic, hormonal, vascular insufficiency, chronic inflammation, dietary and neurological effects. Clinical evaluation and associated conditions are important for assessing the severity of cellulite and are useful for determining various treatment options. To date, cellulite treatment still a challenge, require long-term stability of influencing factors.